Liquid Biopsy in Pre-Metastatic Niche: From Molecular Mechanism to Clinical Application - Liu, Zaoqu; Kong, Ying; Dang, Qin; Weng, Siyuan; Zheng, Youyang; Ren, Yuqing; Lv, Jinxiang; Li, Na; Han, Yilin; Han, Xinwei (Frontiers in Immunology, 2022)
Metastatic dissemination represents a hallmark of cancer that is responsible for the high mortality rate. Recently, emerging evidence demonstrates a time-series event — pre-metastatic niche (PMN) has a profound impact on cancer metastasis. Exosomes, cell-free DNA (cfDNA), circulating tumor cells (CTC), and tumor microenvironment components, as critical components in PMN establishment, could be monitored by liquid biopsy. Intensive studies based on the molecular profile of liquid biopsy have made it a viable alternative to tissue biopsy. Meanwhile, the complex molecular mechanism and intercellular interaction are great challenges for the application of liquid biopsy in clinical practice. This article reviews the cellular and molecular components involved in the establishment of the PMN and the promotion of metastasis, as well as the mechanisms of their interactions. Better knowledge of the characteristics of the PMN may facilitate the application of liquid biopsy for clinical diagnosis, prognosis, and treatment.